PENGARUH HABITS OF MIND TERHADAP KEMAMPUAN GENERALISASI MATEMATIS - Gelar Dwirahayu; Dedek Kustiawati; Imania Bidari (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
The purpose: describe of Student's Habits of Mind, and its influence to students’s mathematical generalization at  junior high school particularly in teaching and learning mathematics. Habits of mind is defined as someones’ habits or trends to performed as an intelligent behavioral patterns confronted with the problems that can not be solve easily. There are four categories of Habits of Mind in this research: persisting, thinking, thinking flexibly, and applying past knowledge to new situations. The method is Expose Facto method, conducted a long April and May 2016 with the subject of  research are  students at MTs Negeri 32 Jakarta, class VIII-5 as 38 people. The instruments: questionnaires and test. The result show that correlation between Habits of mind and students’generalization, as  a simple linear regression analysis. At the level of significance α = 0.05 obtained linear regression formula Y = -86,165 + 2,116X.  The coefficient of correlation (r2) = 0,425 and coefficient of determination = 42,5%. Its means that students’ habits of mind that gives positive effect  to students’ mathematical Generalization as 42.5% while 57.5% impact of others. Keywords: Habits of Thinking, Ability of Mathematical Generalization